2015
DOI: 10.2147/cia.s54630
|View full text |Cite
|
Sign up to set email alerts
|

Oral health in the elderly patient and its impact on general well-being: a nonsystematic review

Abstract: Data on the oral health of the elderly depict a worrying situation, with an elevated prevalence of caries and moderate periodontal disease, frequent edentulism, and numerous cases of dry mouth and oral cancer. There is wide evidence that periodontitis is a risk factor for certain systemic diseases, and impaired oral health has been associated with mastication and nutritional problems, especially among the elderly, with highly negative effects on their quality of life. In this nonsystematic review, the authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
330
5
21

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(368 citation statements)
references
References 69 publications
12
330
5
21
Order By: Relevance
“…This contrasts with previous studies of the prevalence of PD and VED that showed an increased prevalence among elderly subjects and those with a lower standard of living [12,13]. These discrepancies might be explained by the reduced accessibility of dental services among that population, and by the limitations of the current https://doi.org/10.5051/jpis.2017.47.2.96…”
Section: Discussioncontrasting
confidence: 70%
“…This contrasts with previous studies of the prevalence of PD and VED that showed an increased prevalence among elderly subjects and those with a lower standard of living [12,13]. These discrepancies might be explained by the reduced accessibility of dental services among that population, and by the limitations of the current https://doi.org/10.5051/jpis.2017.47.2.96…”
Section: Discussioncontrasting
confidence: 70%
“…2). Common oral conditions with age include periodontal disease, oral cancer, candidiasis, and xerostomia, which can lead to other dental conditions like root caries (Gil-Montoya et al, 2015a;Gonsalves et al, 2008). For example, oral cancer alone can be attributed to multiple hallmarks of aging including genomic instability (Bhattacharya & (Sumida & Hamakawa, 2001).…”
Section: Aging and Diseases Of The Oral Cavitymentioning
confidence: 99%
“…We believe that this relationship could be particularly important for both healthspan and lifespan, as age is the major risk factor for several oral health conditions ( (Guiglia et al, 2010), (Razak et al, 2014)), including oral cancer (Gil-Montoya et al, 2015a), xerostomia (dry mouth) (Navazesh, 2002), and periodontal disease. These chronic conditions can significantly detract from quality of life for the elderly and have been linked to increased risk for a variety of co-morbidities.…”
Section: Introductionmentioning
confidence: 99%
“…생애주기 중 특히 노인은 음식섭취의 장애, 발음장애, 통증 유발 등 구강 건강 상태에 의해 일반적 건강, 행복감, 우울 및 삶의 질에 크게 영향을 받는다 2,3) . 노인에서 발생하는 자연치아 상실, 신체동작의 조정력 약화, 저작근의 약화 등은 저작능력을 감소시키고 4) , 노인의 물리적, 생리적, 심리학적, 감정적 특 성을 변화시킬 수 있다 5) .…”
Section: 서 론unclassified